Predictive value of c-erbB-2, p53, cathepsin-D and histology of the primary tumour in metastatic breast cancer. - Niskanen, E. (Nature Publishing Group, 1997)
The value of various prognostic factors in breast cancer patients has been determined in a number of studies. Few reports have been published on the dependence of treatment outcome on histological and immunohistochemical characteristics in the primary tumour in patients with metastatic disease. We studied the incidence and prognostic value of histological and molecular abnormalities in the primary tumour of patients who had developed metastatic breast cancer. Eligible patients received a fluorouracil, epirubicin and cyclophosphamide (FEC) regimen either once a week or once every 4 weeks. Adequate specimens for various analyses were available from 127 patients. Median follow-up time of the patients ranged from 15 to 101 months. In this study, the histological grade of the malignancy best predicted response to chemotherapy (P < 0.0005). Most of the responses were observed in patients with grade 1 tumours; in this group, time to progression was delayed. C-erb B-2 gene amplification and oncoprotein expression had no predictive value. Neither p53 nor cathepsin-D predicted treatment outcome after chemotherapy. None of the factors had an effect on overall survival. Among breast cancer patients who received anthracycline-containing chemotherapy, response to treatment correlated with histological grade. In patients with histological grade 1 breast cancer, the time to progression was longest. However, overall survival was not affected by histological grade nor the other parameters tested. In addition to histological grade, other prognostic factors that are not included in this study need to be identified to determine which patients with metastatic breast cancer would benefit from cytotoxic treatment.